Peer effects in secondary education: Evidence from trends in mathematics and science study 2015 based on weak-tie bonds - Bernhard C. Dannemann (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Peer effects in education production functions are predominantly employed as the mean classroom performance. Based on sociological theory and using spatial regression techniques, I introduce social network matrices that correspond to a weighting scheme for peers within the class. In a spatial regression, I show the presence of peer effects for the 8th grade population in the USA in the TIMSS 2015 student assessment. For students, the likelihood of cooperation increases conditional on visible and non-visible characteristics, i.e., age, gender, foreign origin, or scholastic achievement. Externalities of scholastic performance show a larger magnitude than the direct effects on the individual. The results are robust to various definitions of how peer groups are created, e.g., classroom-average, status homophily or value homophily and to the inclusion of school level fixed effects.
Keywords: I21; D62; C31; C18; D91; 330; Human Capital; Cognitive Skills; Peer Effects; Spatial Model; Class Heterogeneity; Education Production Function